Photocatalytic reactors - M. Bouchy; O. Zahraa (International Journal of Photoenergy)
Fundamental concepts for the design of photocatalytic reactors are recalled: specific rate, modeling of the distribution of the irradiation, description and modeling of transport phenomena on the macroscopic and macroscopic scales. These are required for establishing the reactor mass balance. A brief survey of various reactors is given for solar or artificial light, gas- or liquid-phase, slurry or fixed-bed.